Navigating English Learning with AI: A Qualitative Study of University Students Experiences - Febriani, Hanura (PPSDP International Journal of Education, 2024)
The accelerated development of Artificial Intelligence (AI) technologies has had a substantial impact on educational practices, particularly in the field of English education. This study investigateshe experiences of university students at a UIN Fatmawati Sukarno Bengkulu in the process of navigating English learning through AI. The study examines the challenges and benefits those students experience when utilizing the most frequently used AI tools, as well as their perceptions of these technologies. Interviews with nine students in the fifth semester of the English program at UIN Fatmawati Sukarno Bengkulu are conducted using a qualitative methodology. The results indicate that students have a positive attitude toward AI in the context of English learning and employ a variety of AI tools to resolve various aspects of language acquisition. This study is a unique exploration of the manner in which university students simultaneously incorporate multiple AI tools in their English learning, providing new insights into the role of AI in promoting self-directed learning and practical language application. The study offers new insights into the transformative potential of AI in supporting students’ autonomous learning journeys while learning English by providing a comprehensive view of AI’s role in English education.